Energy Poverty and Entrepreneurship - Zhiming Cheng; Massimiliano Tani; Haining Wang (Institute of Labor Economics (IZA), 2021)
We use the 2012-2018 China Family Panel Studies data to examine the relationship between household energy poverty and an individualâ exteuro™s probability of becoming an entrepreneur. Consistent with the theory of underdog entrepreneurship that negative personal circumstances can foster self-reliance, resourcefulness and other skills and personality traits conducive to entrepreneurship, we find that spending a higher share of household income on energy consumption or being energy poor increases the probability of being an entrepreneur. The results are robust to various checks, including alternative measures of energy poverty, non-linear effects of the share of energy spending in household income, past entrepreneurial experience, alternative estimation methods and potential omitted variable bias. We also explore the channels through which energy poverty influences whether one chooses to become an entrepreneur. We find that cognitive functions, mental health and self-confidence negatively mediate, while self-belief, extroversion and openness positively mediate, the relationship between energy poverty and entrepreneurship.
Keywords: I32; L26; Q41; 330; entrepreneurship; energy poverty; China